Cost-Effectiveness of New Direct-Acting Antivirals to Prevent Post–Liver Transplant Recurrent Hepatitis - Cortesi, P. A. (Am J Transplant, 2015)
Preliminary studies on HCV-cirrhotics listed for transplant suggest that Sofosbuvir in combination with Ribavirin is very effective in promoting viral clearance and preventing disease recurrence. Unfortunately, the high cost of such treatment (€46 500 per 12 weeks treatment) makes its cost-effectiveness questionable. A semi-Markov model was developed to assess the cost-effectiveness of Sofosbuvir/Ribavirin treatment in cirrhotic patient without HCC (HCV-CIRRH) and with HCC (HCV-HCC) listed for transplant. In the base-case analysis, the incremental cost-effectiveness ratio for 24 weeks of Sofosbuvir/Ribavirin was €44 875 per quality-adjusted life-year gained in HCV-CIRRH and €60 380 in HCV-HCC patients. Both results were above the willingness to pay threshold of €37 000 per quality-adjusted life-year. Our data also show that in order to remain cost-effective (with a 24 weeks treatment), any novel interferon-free treatment endowed with ideal efficacy should cost less than €67 224 or than €95 712 in HCV-cirrhotics with and without HCC, respectively. The results shows that Sofosbuvir/Ribavirin therapy, given to patients listed for transplant, is not cost-effective at current prices despite being very effective, and new, more effective treatments will have little economic margins to remain cost-effective. New interferon-free combinations have the potential to revolutionize the treatment and prognosis of HCV-positive patients listed for transplant; however, without sustainable prices, this revolution is unlikely to happen.